Ginger (Zingiber officinale) powder from low temperature drying technique - Sarker, AK; Rashid, M; Roy, DC; Musarrat, M; Bithi, UH (Bangladesh Journal of Scientific and Industrial Research, 2021)
Ginger powder was prepared using different low temperature drying techniques and their nutritional, phytochemicals, functional and sensory quality were investigated. Moisture content was significantly (p<0.05) higher (7.16±0.04%) in shade dried powder and lowest in oven dried powder. Protein, fat and fiber contents varied with drying techniques ranging from 6.08±0.05 to 6.68±0.07%, 1.08±0.16 to 1.39±0.25% and 3.86±0.13 to 5.11±0.06% respectively. Highest alkaloid content was found in mechanical dried powder (4.44±0.04%), while highest flavonoid content was found in oven dried ginger powder (4.67±0.07%) and maximum saponin content was recorded in shade dried powder (2.67±0.10%). Highest ascorbic acid content (3.53±0.08 mg/100g) was found in shade dried powder and lowest was recorded in oven dried ginger powder (3.53±0.08 mg/100g). Sun drying technique exhibited better nutritional and sensory quality. The sensory score demonstrated that acceptance of all dried ginger powder was in the range of liked very much to liked moderately by the panelist. Low temperature drying techniques have positive significance on retaining phytochemicals and sensory quality of processed ginger. Bangladesh J. Sci. Ind. Res.56(2), 133-140, 2021